Exploring the Relationship between Adolescent Activities and Choice of Graduate School Discipline: Implications for Creativity Development. (2nd August 2014) - Hartzell, Stephanie A.; Hong, Eunsook
Abstract : The relationship between adolescent extra‐curricular activities and choice of graduate‐education field was examined among students from three fields of study, science ( n  = 12), art ( n  = 12), and education ( n  = 14), using qualitative and quantitative methods. Results of profile analysis indicated that the different majors participated in stereotypically varying activities when they were adolescents. Science majors generally participated in mathematics and science activities during adolescence. Art majors generally participated in theater and music activities, and education majors tended to have participated in social leadership and educational activities. Interviews with the participants supported these findings and provided a more comprehensive discussion of these tendencies. While in high school, the participants had many influences when determining a field of study. Using personal happiness as a guide, the participants chose activities and ultimately graduate‐level majors that reflected their interests. It was concluded that adolescent extra‐curricular activities are important in the development of interest in creatively talented individuals and may lead to graduate field selection.